Revitalization and Transformation of Balinese Society Local Wisdom in the Legal Development - Gelgel, I Putu (International Research Journal of Management, IT & Social Sciences, 2017)
Balinese society local wisdom had a high potential for the legal development, both in the legal substantive development and the legal structure, as well as legal culture. It was a social reality was understood and implemented in their life, in fact, a very functional in the society. Therefore, it needs to be revitalized and transformed into national legal development. The revitalization of the local wisdom potential of Balinese society in legal development. It was conducted by way of leveraging the performance of Desa Adat organization unlike Bendesa policy, Kelihan, Pecalang with doing a cooperation and coordination towards government agencies, especially the state of legal enforcement in carrying out the task in a manner with the wise and prudent, a good attitudes and no arrogance as well as a violence. Therefore, the attitude of legal enforcement officials would be role models for the societies. Thus, the Bali image as the island was safe, orderly, and peaceful, with the population-paced of harmony could be preserved. The transformation of Balinese local wisdom was done by accommodating in the local regulation, even the regulation of provincial level regional as well as the regency and city level.